2017
DOI: 10.1021/acsami.7b07960
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Solar Cells Based on Two Small Molecule Donors with Same Conjugated Backbone: The Role of Good Miscibility and Hole Relay Process

Abstract: Ternary organic solar cells (OSCs) are very attractive for further enhancing the power conversion efficiencies (PCEs) of binary ones but still with a single active layer. However, improving the PCEs is still challenging because a ternary cell with one more component is more complicated on phase separation behavior. If the two donors or two acceptors have similar chemical structures, good miscibility can be expected to reduce the try-and-error work. Herein, we report ternary devices based on two small molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…[73,79,80] The PBDB-T:IEICO-4F:3TT-FIC-based ternary PSCs exhibited high J ph and low J sat values, which account for the efficient photocurrent response and the sharply saturated state. [81,82] The slight reduction in the G max value of PBDB-T:IEICO-4F:3TT-FIC-based ternary PSCs is consistent with the blueshift of the absorption peaks of PBDB-T:IEICO-4F:3TT-FIC ternary films compared with PBDB-T:IEICO-4F binary films. In addition, the highest η diss and η coll values of PBDB-T:IEICO-4F:3TT-FIC-based ternary PSCs indicates efficient exciton dissociation at the PBDB-T/blend acceptor triple interface and charge carrier transport and collection between the photoactive layer and the electrode.…”
Section: Wwwadvopticalmatdesupporting
confidence: 66%
“…[73,79,80] The PBDB-T:IEICO-4F:3TT-FIC-based ternary PSCs exhibited high J ph and low J sat values, which account for the efficient photocurrent response and the sharply saturated state. [81,82] The slight reduction in the G max value of PBDB-T:IEICO-4F:3TT-FIC-based ternary PSCs is consistent with the blueshift of the absorption peaks of PBDB-T:IEICO-4F:3TT-FIC ternary films compared with PBDB-T:IEICO-4F binary films. In addition, the highest η diss and η coll values of PBDB-T:IEICO-4F:3TT-FIC-based ternary PSCs indicates efficient exciton dissociation at the PBDB-T/blend acceptor triple interface and charge carrier transport and collection between the photoactive layer and the electrode.…”
Section: Wwwadvopticalmatdesupporting
confidence: 66%
“…Moreover, the newly designed small molecule does not display an obvious vibronic shoulder peak unlike the other two donors, suggesting weak intermolecular interactions between the conjugated backbones or decreased degree of molecular aggregation. [24,37] Adv. The HOMO/LUMO levels were calculated from the onset oxidation and reduction potential ( Figure S2, Supporting Information) as −5.33 eV and −3.50 eV, respectively, which indicate a significant reduction when compared with energy levels of DCAO3TBDTT and DR3T-BDTT.…”
Section: Design Synthesis Optical and Electrochemical Propertiesmentioning
confidence: 99%
“…Actually, incorporating a structurally similar donor to the binary system is also considered as an effective way to enhance the photovoltaic performance . Previously, Peng and co‐workers have reported that the synergistic effects of the two structurally similar donors including good miscibility and hole relay process have played a critical part in facilitating the charge transportation for the ternary system . Recently, we have also reported a type of all‐small‐molecule ternary solar cell consisting of two compatible small molecules as donors and PC 71 BM as the acceptor .…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] And the expanded and enhanced absorptions in J-aggregation-based films provide the potential chance to fabricate broader light response and larger short-circuit current (J SC ) solar cell devices. Some of porphyrin derivatives are near-infrared (NIR) organic semiconductors with optical bandgap less than 1.5 eV which have attracted much attention due to their great contribution to the field of NIR photodetector, 29,30 SM-OSCs, [31][32][33][34][35][36][37][38][39][40][41] ternary solar cells [42][43][44][45][46] and tandem solar cells. 47,48 In this contribution, we report dimer porphyrin molecule ZnP2-DPP 49 (Figure 1 .…”
Section: Introductionmentioning
confidence: 99%